Posted by
**Jasmine20** on
.

Directions:Multiply

Problem:

((x)/(3)+(3)/(4)) ((3x)/(4)-(3)/(5))

so the answer for it i got:

((20x^2+20x-36)/(80))

I worked it and I have what you have EXCEPT 29x instead of 20x. If you can't find the error, post your work and we can help you find it.

PLEASE HELP ME FIND MY ERROR....THIS IS WHAT I DID.

Directions:Multiply

Problem:

((x)/(3)+(3)/(4)) ((3x)/(4)-(3)/(5))

The steps i took:

First i simplify between (x)/(3) and (3)/(4) the common denominator is 12.

Then multiplied: x(4) and 3(3)= ((4x+9)/(12))

between (3x)/(4) and (3)/(5) the common denominator is 20.

so then i multiplied: 3x(5) and 3(4)=

(15x-12)/(20)

Now i have:((4x+9)/(12))((15x-12)/(20))

NOw i multiplied: ((4x+9)(15x)/(240))

now i factored out a 3 out of the top to get:

3((4x+9)(5x-4)/(240))

now i simplify again:

((4x+9)(5x-4)/80)

now foil the top:

f=4x(5x)

o=4x(-4)

i=9(5x)

l=9(-4)

(4x+9)(5x-4)

=4x(5x)+4x(-4)+9(5x)+9(-4)

=20x^2-16x+45x-36

=20x^2+20x-36

NOW i just put that back in:

((4x+9)(5x-4)/(80))

so that's how i came up with:

((20x^2+20x-36)/(80))

((x)/(3)+(3)/(4)) ((3x)/(4)-(3)/(5))

The steps i took:

First i simplify between (x)/(3) and (3)/(4) the common denominator is 12.

Then multiplied: x(4) and 3(3)= ((4x+9)/(12))

between (3x)/(4) and (3)/(5) the common denominator is 20.

so then i multiplied: 3x(5) and 3(4)=

(15x-12)/(20)

Now i have:((4x+9)/(12))((15x-12)/(20))**ok to here.**

NOw i multiplied: ((4x+9)(15x**-12**)/(240))
**you dropped the -12**

now i factored out a 3 out of the top to get:

3((4x+9)(5x-4)/(240))

now i simplify again:

((4x+9)(5x-4)/80)

now foil the top:

f=4x(5x)

o=4x(-4)

i=9(5x)

l=9(-4)

(4x+9)(5x-4)

=4x(5x)+4x(-4)+9(5x)+9(-4)

=20x^2-16x+45x-36

=20x^2+20x-36

OKAY I DON'T SEE IT CAN YOU EXPLAIN TO ME WHAT AM I SUPPOST TO DO.OR WHAT SHOULD IT LOOK LIKE

NOw i multiplied: ((4x+9)(15x**-12**)/(240))
**you dropped the -12.
(4x+9)(15x-12)/240 =
FOIL it.
(60x^2 -48x +135x -108)/240 =
Combine terms.
(60x^2 + 87x -108)/240 =
Divide by 3.
(20x^2 + 29x -36)/80 =**

*I don't know how your are to leave it in final form but I'm sure you can take it from here.*

now i factored out a 3 out of the top to get:

3((4x+9)(5x-4)/(240))

now i simplify again:

((4x+9)(5x-4)/80)

now foil the top:

f=4x(5x)

o=4x(-4)

i=9(5x)

l=9(-4)

(4x+9)(5x-4)

=4x(5x)+4x(-4)+9(5x)+9(-4)

=20x^2-16x+45x-36

=20x^2+20x-36

I appreciate all your help....especially correcting my wrongness.